A Study of the Concept of Qiwamah in Surah Al-Nisa’ (4): 34 From the Perspectives of Kecia Ali and Khaled M. Abou El-Fadl - Daib Insan Labib, Muhammad Alfreda; Fajriyaturrohmah (Al-Basirah Journal, 2023)
This article discusses about; 1). Analysis of the meaning of qiwāmah and its derivation in the al-Qur’an. 2). Analysis of qiwāmah from the perspective of hadith and Salaf and contemporary scholars. 3). Interpretation of qiwāmah according to Kecia and Khaled. This research uses a descriptive comparative analysis method by collecting and describing literature related to the discussion study, then analyzing the data. This article concludes that Kecia Ali believes that men cannot be said to be qawwām in the household as long as both parties have a role and contribution in household finances in a modern context, while Khaled argues in Surah Al- Nisā’ 34 that men and women are positioned according to the actions and efforts undertaken so that it does not rule out the possibility that women can become qawwām for men.